Python for teenagers : learn to program like a superhero! - Payne, James R. (Apress, 2019)
Discover everything you need to learn Python programming, with fun examples along the way. This book gives you ideas for how to turn your love of programming into a job you'll love. Start with the basics and before you know it, you'll be building your own web sites, doing white-hat hacking, finding code bugs and errors, and creating games, including using Python to roll characters for RPGs. Every chapter is relaxed and informal, like learning with a cool teacher all the time. Computers, phones and the web are your playground, and you'll be ready to join the party with your own content. Going beyond posts and uploads means learning to program, and Python is a great choice to get started. It's quick to learn, it's flexible, and if you want, it may get you a Python job that pays more than minimum wage when you're out of school. Python for Teenagers is the most fun you'll have while learning.